Implementation of Smart Models to Improve Student Activities and Learning Outcomes - Mohammed Mahdianur, Desi Dvitalia Saari (GLOBAL SCIENTS PUBLISHER, 2024)
The problem in this study is the low activity and learning outcomes of students at SDN Kelayan Selatan 3. The purpose of this study is to describe teacher activities, analyze student activities and student learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (PTK), with 4 meetings. The setting of this research is grade IV students in the even semester of SDN Kelayam Selatan 3 for the 2022/2023 academic year. The results of the research that have been carried out show that the teacher's activity in meeting 1 reached 75% of the